2018
DOI: 10.1002/j.2334-5837.2018.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

A Tailoring of the Unified Architecture Framework's Meta‐Model for the Modeling of Systems‐of‐Systems

Abstract: Being used by single companies and by coalitions of governments at the same time, Architecture Frameworks have spread widely as a key tool for the enablement of the Model Based Systems Engineering approach. The Unified Architecture Framework, promoted by the Object Management Group, is rapidly emerging as the reference framework to describe Enterprise Architecture, providing a standard representation for both defense and non‐defense organizations’ architecture descriptions. The work described in the present pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…DoDAF, MODAF, and NAF were primarily created for the defense industry, making it difficult to apply them to other industries due to the lack of security and humanmachine integration views [7], [9], [10]. Moreover, crosscountry projects throughout NATO nations highlighted the need for a unified architecture to yield the greatest benefits [9] since interoperability between architectures created by various entities is becoming more and more necessary [11]. Therefore, the Object Management Group (OMG) developed the Unified Architecture Framework (UAF) as a unified architecture for DoDAF, MODAF, and NAF to be applicable to both military and commercial enterprises [9], [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DoDAF, MODAF, and NAF were primarily created for the defense industry, making it difficult to apply them to other industries due to the lack of security and humanmachine integration views [7], [9], [10]. Moreover, crosscountry projects throughout NATO nations highlighted the need for a unified architecture to yield the greatest benefits [9] since interoperability between architectures created by various entities is becoming more and more necessary [11]. Therefore, the Object Management Group (OMG) developed the Unified Architecture Framework (UAF) as a unified architecture for DoDAF, MODAF, and NAF to be applicable to both military and commercial enterprises [9], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, crosscountry projects throughout NATO nations highlighted the need for a unified architecture to yield the greatest benefits [9] since interoperability between architectures created by various entities is becoming more and more necessary [11]. Therefore, the Object Management Group (OMG) developed the Unified Architecture Framework (UAF) as a unified architecture for DoDAF, MODAF, and NAF to be applicable to both military and commercial enterprises [9], [11]. Tirone et al [11] depict the evolution of architecture frameworks since 1987 and how they unified and resulted in the UAF in 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tirone et al, 2018 discussed this issue and concluded that any entity which can be subject of "Architecture" should be the target of the UAF. The entity whose architecture is defined can be any: enterprise, system of systems, collection of systems, product line, individual system, portion of a system, product, service, individual hardware or software item, any other entity that is amenable to architectural definition (eg, data, doctrine, organization, process, method, technique, policy, facilities, etc) [Martin, 2016] The works reported within the literature [Tirone et al, 2018, Morkevicius et al, 2017 describes the tailoring of UAF to describe the architecture of system of systems. But those works do not describe any step by step method to build a system model necessary to give a clear guidance to system architects.…”
Section: Introductionmentioning
confidence: 99%
“…The UAF Based MBSE (UBM) method described within this paper uses a selected subset from the UAF domain model and defines a step by step procedure to construct the system model. The tailoring of UAF proposed by Tirone et al, 2018 selects the same perspectives as UBM, but they customize the UAF profile by adding some specific stereotypes as, System of Interest, Actor and Use Case. We use the UAF profile without customizations and provide the mapping between UAF elements and the common terms used by system engineers.…”
Section: Introductionmentioning
confidence: 99%